TOBACCO CESSATION COUNSELLING FOR WOMEN IN RURAL SINDH: IS IT BEING OFFERED? - Ali, Sajid; Naqvi, Sadaf A; Ali, Arif (Journal of Ayub Medical College Abbottabad, 2011)
Background: Tobacco is the single leading and most preventable cause of death in today’s worlds and responsible for six of the eight leading mortality causes in the world. Diseases related to tobacco use are known to cause about 5.4 million deaths every year, 80% of which are contributed by the developing world, and this toll is estimated to increase up to 8 million deaths per year by 2030. This study was conducted to determine the number of women who were offered counselling regarding cessation of tobacco use by all health care providers (medical and alternate), in rural Sindh, Pakistan. Methods: This cross-sectional survey was conducted during January to March, 2008 in District Khairpur, Sindh, Pakistan. A validated, pre-tested, translated questionnaire was used to collect the data from 502, adult women (aged between 18-60 years). These women were asked about the type of health provider they visited in the past 12 months and practices of provider regarding tobacco control including cessation and advice. Results: A large majority of women (nearly 71%) were illiterate, and 44% of women were in the age group 18-24 years. High prevalence (10%) of adult women were smokers. Only 12% of the total women who visited physicians during this time period were asked about their smoking status as compared to 7% who visited hakims and 13% who were approached by lady health visitors. Conclusion: A very small segment of the women users of health care system is enquired and counselled about tobacco use in any form by the health providers in Rural Sindh. Revisiting practices for health care professionals is urgently needed to address inevitable tobacco use in the region. Keywords: Tobacco, Women, Pakistan, Health Care Provider, Smoking, Control, Rural Sindh